2006
DOI: 10.1142/s1363919606001417
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Innovation on Intellectual Capital: An Empirical Evaluation in the Biotechnology and Telecommunications Industries

Abstract: This research studies how innovation competences affect the stock of intangibles and facilitate the development of intellectual capital (IC). We develop a theoretical model with these constructs, in which we distinguish two dimensions within innovation competences — Schumpeterian and continuous improvement competences; and three dimensions for IC — human capital, structural capital and relational capital. Theoretical relations are tested in an empirical study carried out in 222 Spanish firms from the Biotechno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Lastly, since innovation is intrinsically grounded in knowledge, future research could explore the influence of innovation on strengthening IC. Indeed, Marqués et al () suggested that it is innovation that actually feeds IC, rather than the other way around. Case study methodology could be applied to examine the causality of the innovation–IC linkage in depth, which might offer valuable insights concerning the ways innovation affects a company's knowledge base.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, since innovation is intrinsically grounded in knowledge, future research could explore the influence of innovation on strengthening IC. Indeed, Marqués et al () suggested that it is innovation that actually feeds IC, rather than the other way around. Case study methodology could be applied to examine the causality of the innovation–IC linkage in depth, which might offer valuable insights concerning the ways innovation affects a company's knowledge base.…”
Section: Discussionmentioning
confidence: 99%
“…Innovation may in turn affect the stock of intangibles and facilitate the development of IC (Marqués, Simón, and Carañana, 2006). Several studies contend that the process of innovation enhances the knowledge, skill, and experience of employees (Amadi-Echendu, 2007), improves the organizational structure, mechanisms and capabilities (O'Connor, 2008), and strengthens the embedded relationships (Guevara and Bounfour, 2013).…”
Section: Three Alternative Modelsmentioning
confidence: 99%
“…A successful strategy will only be feasible if it is constructed on the basis of the relative strengths of the firm. To measure innovation distinctive competences, we take previous work by Palacios et al (2006) as our base. This scale measures innovation distinctive competences by means of a subjective semantic scale, based on the self-classification by managers of their firm in relation to its competitors.…”
Section: Innovation Distinctive Competencesmentioning
confidence: 99%
“…These scales meet the sociometric conditions (dimensionality, reliability and validity) required for measurement scales in social sciences. In the article by Palacios et al (2006), you can see the list of items that make up the innovation distinctive competences scale.…”
Section: Innovation Distinctive Competencesmentioning
confidence: 99%